Activities of Some Degrading Enzymes During Decomposition of Pearl Millet and Wheat Straw - Meena, S C; Panwar, Jitendra; Tarafdar, J C; Kumar, Praveen; Kathju, S (Annals of Arid Zone, 2016)
A pot experiment was conducted with wheat and pearl millet straw (4 and 8 t ha-I) placed either on surface or at 12 cm depth and maintained at 50% water holding capacity (WHC) in a Camborthid loamy sand soil. The changes in different enzyme activities (dehydrogenase, acid phosphatase, alkaline phosphatase, cellulase, protease and transaminase) were measured at 15-day interval up to 120 days. Straw incorporation significantly influenced activities of all the enzymes. In general, the activities of enzymes were highest after 15 days, except transaminase activity, which was maximum at 30 days in all the straw incorporated soil samples. Protease and transaminase activities were not detected after 45 days and 69 days, respectively. A strong correlation of dehydrogenase activity (total microbial activity) with acid phosphatase, alkaline phosphatase, cellulase, protease and transaminase activity was observed. Sub-surface placement (12 cm depth) of straw resulted in greater enzyme build up than did surface placement. Only marginal C- build up in soil was noticed after 4 months of straw incorporation.